Analysis of the Implementation of E-Learning in Melajah.id Using Human Organization Technology (HOT) Fit Model - Gusti Komang Pradhana; Gede Rasben Dantes; Dewa Gede Hendra Divayana (Information Technology and Science (ITScience), 2023)
This research is motivated by the absence of prior analysis on the success level of implementing Melajah.id e-learning and the performance analysis of the e-learning platform from the perspective of human, organizational, and technological support aspects. Therefore, the existence of this scholarly research is considered necessary as a consideration for stakeholders involved in the policy-making for the development of educational service quality in vocational schools. The purpose of this research is to assess the performance and success level of the implementation of the Melajah.id e-learning platform in use at SMK Negeri 3 Tabanan. For the indicators of the human variable, they include: (a) System Use and (b) User Satisfaction. For the indicators of the organizational variable, they include: (a) Organization Structure and (b) Organization Environment. As for the indicators of the technology variable, they encompass: (a) System Quality, (b) Information Quality, and (c) Service Quality. Data collection for the research was conducted through the distribution of online questionnaires using Google Forms, while supplementary data was obtained through observation and interviews to gather information that could not be revealed through questionnaires. Subsequently, the data analysis approach used to measure the success and performance of the e-learning system implementation was linear regression analysis as the quantitative method. Furthermore, qualitative data analysis was performed through content analysis of interview scripts and interpretation of observational data (photos and videos). The combination of the results from quantitative and qualitative analyses served as the basis for drawing conclusions and making recommendations regarding the analysis of the success of the Melajah.id e-learning implementation in the vocational school where the research was conducted.